Antihypertension Activity of Averrhoa bilimbi Fruit Juice on Sodium Chloride and Prednisone-Induced Rats - Yuniarto, Ari; Alviolita, Dini; Kurniasukmawati, Ika; Rasydy, La Ode Akbar (MPI (Media Pharmaceutica Indonesiana), 2023)
Hypertension is a condition where systolic and diastolic blood pressure continuously increases, causing heart disease, kidney disease, hardening of the arteries, eye damage, and stroke (brain damage). Bilimbi (Averrhoa bilimbi L.) is traditionally used to lowering high blood pressure. The research objective was evaluating the activity of A. bilimbi as an antihypertensive. The research was conducted in vivo using rats and the CODA blood pressure analysis instrument. The doses used for A. bilimbi juice were 150, 300, and 600 mg/kg BW, respectively. A. bilimbi juice at a dose of 600 mg/kg BW/day for 14 days can reduce systolic and diastolic blood pressure in male Wistar rats induced by 2.5% NaCl and 1.5 mg/kg BW prednisone. The results of the study showed that A. bilimbi juice at a dose of 600 mg/kg BW. had antihypertensive activity.